A statistical mechanics approach to cultural evolution of structured behavior in non-human primates: From disorder to tetris-like structures. (1st November 2022) - Vera, Javier; Fuentealba, Diego; Lopez, Mario; Ponce, Hector
Abstract: This paper explores a statistical mechanics approach to cultural evolution of structured behavior in non-human primates. Previous works on cultural evolution have proposed Iterated Learning procedures, in which the behavioral output of one individual becomes the target behavior for the next individual in the chain. Within this line of research, previous work has suggested that even in non-human primates this paradigm shows that cultural transmission can lead to the progressive emergence of tetris-like structures. Our simulations are based on several interrelated statistical mechanics measurements, which quantify the way structures become closer to each other and the tendency to put activated cells together (understood by means of a number of measures and an energy-like function). With these tools, we suggested the hypothesis that the appearance of tetris-like structures might be an indirect consequence of the energy-like minimization. From this, it is plausible to think that the preference of the participants for tetris-like structures is strongly related to some kind of minimization towards simplicity in cognition.